2021
DOI: 10.3329/baj.v24i1.55545
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Yield Responses of Some Selected Rapeseed/Mustard Genotypes to Salinity Stress

Abstract: An experiment on rapeseed/mustard genotypes was conducted during 2019-2020 rabi season in vinyl house of Plant Physiology Division of Bangladesh Agricultural Research Institute (BARI), Gazipur to find out the salt-tolerant genotypes based on the responses of their physiological parameters and yield. Five selected rapeseed/ mustard genotypes (V1= Jun-536, V2 = BJDH-12, V3 = BD-10115, V4 = BARI Sarisha-14, V5 = BD-6950) were tested at three salinity levels (S0= 0, S1= 5 and S2=10 dS m-1). Irrespective of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The data on mustard seed and straw yield, presented in Table 3 and 4, revealed that the seed and straw yield of different mustard varieties decreased with increasing levels of irrigation ion imbalance (Singh and Panda, 2012). Our results are in conformity with the findings of previous studies (Bybordi., 2010;Kripa et al, 2011;Toorchi et al, 2011;Rameeh, 2013 andZaman et al, 2015;Ahmed et al, 2021). 54.54 q ha ) and CS 2009-313 (15.28 and 44.96 q ha ),…”
Section: Resultsmentioning
confidence: 99%
“…The data on mustard seed and straw yield, presented in Table 3 and 4, revealed that the seed and straw yield of different mustard varieties decreased with increasing levels of irrigation ion imbalance (Singh and Panda, 2012). Our results are in conformity with the findings of previous studies (Bybordi., 2010;Kripa et al, 2011;Toorchi et al, 2011;Rameeh, 2013 andZaman et al, 2015;Ahmed et al, 2021). 54.54 q ha ) and CS 2009-313 (15.28 and 44.96 q ha ),…”
Section: Resultsmentioning
confidence: 99%